Ensaios triaxiais de compressão e extensão na argila cinza do Rio de Janeiro em Botafogo - Lins, Amaro Henrique Pessoa (1980)
This dissertation deals with the deterrnination of stress-strain-strength parameters of a medium clay layer at an exavation site of the Rio de Janeiro subway at Botafogo, section 09, through compression and extension consolidated-undrained triaxial tests. The disturbance of the block soil samples was dealt with by means of the SHANSEP Method, which requires consolidation of the soil specimens under effective stresses several times higher than the existing field effective stresses. Through the "Normalized Parameters" approach of the Method, field conditions can be estimated with a better degree of confidence. Parameters obtained from extension and compression triaxial tests were compared. The hyperbolic forrnulation for the stress-strain curves suggested by Kondner (1963) and developed by Duncan and Chang (1970) was used, and the tangent moduli were compared with those obtained by Ortigão and Lacerda (1979) with the Rio de Janeiro soft grey clay. These informations will be used in a forthcoming Finite Element analysis that will simulate the subway excavation at that site.